MMP-CG-PET: THE PARAMETER ESTIMATION TECHNIQUE APPLIED TO THE MMP CODE WITH THE METHOD OF CONJUGATE GRADIENTS - Hafner, Ch. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
The Parameter Estimation Technique (PET) is presented as a new technique that can be applied to numerical codes based on dense matrices as a power booster for the computation of frequency plots, etc. In this paper it is applied to the Multiple Multipole Program (MMP) in conjunction with the method of Conjugate Gradients (CG) for iteratively and efficiently solving the rectangular MMP matrix. The PET takes advantage of the a priori knowledge obtained from previous computations and allows to a dramatic reduction of the computation time in various situations. It is demonstrated that one of the most important drawbacks in the use of frequency domain methods based on dense matrices as opposed to time domain methods based on iterative techniques can be eliminated using PET. [Vol. 9, No. 3 (1994), Special Issue on Generalized Multipole Technique (GMT), pp 28-38]